The Effectiveness of a Program Visualization Tool on Introductory Programming: A Case Study with PythonTutor - Oscar Karnalim; Mewati Ayub (CommIT (Communication and Information Technology) Journal, 2017)
Program Visualization (PV) is an educational tool frequently used to assist users for understanding a program flow. However, despite its clear benefits, PV cannot be incorporated easily on Introductory Programming course. Several key properties such as student characteristics and behavior should be considered beforehand. This paper is intended to provide an empirical review about the impact of PV toward students of Introductory Programming course. For our case study, PythonTutor is selected as a sample of PVs due to its accessibility. It can be accessed anywhere and anytime through a web browser. Three conclusions are obtained based on our evaluation on data collected from a survey. Firstly, PV is quite effective to assist students for conducting several programming sub-tasks. Secondly, PV, at some extent, may help students to learn advanced topics on Introductory Programming course. Finally, despite the fact that several features should be incorporated to enhance understanding of students, PV is beneficial for learning Introductory Programming course, especially when it is frequently used.